Osteocardiology Cardiac Bone Formation - Rajamannan, Nalini M. (Springer International Publishing, 2018)
This book describes the field of osteocardiology, an exciting and new sub-discipline within cardiovascular science, which will become the cornerstone for defining the timing and treatment of cardiovascular calcification in the future. With the advent of large cohort databases and experimental mechanistic studies, research has elucidated evidence confirming that traditional cardiovascular risk factors are responsible for the development of atherosclerotic calcification and identified the critical elements of atherosclerosis, including foam cell formation, vascular smooth muscle cell proliferation and extracellular matrix synthesis, which over time forms bone in the heart. Osteocardiology: Cardiac Bone Formation is a practical overview of bone formation in the heart and is destined to become the cornerstone for education of medical students, residents, fellows, graduate students, physician scientists and scientists, for future research and ongoing development in medical therapies to slow or halt the progression of bone formation in the heart.